2013
DOI: 10.4103/2231-0738.106982
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of phosphate-solubilizing bacterial species from different crop fields of Salem, Tamil Nadu, India

Abstract: Phosphate-solubilizing bacterial strains (PSB) were isolated from maize, onion, jasmine, and tomato rhizosphere soils from four different localities of Salem (Tamil Nadu) -(i) Ammapalayam, (ii) Attayampatty, (iii) Seeragapadi, and (iv) Ariyanoor. Twelve efficient PSB isolates were selected from the colonies based on their ability to form clear zone on Pikovskaya's agar medium. The isolated PSB released high amount of phosphorus from calcium phosphate. The efficient bacterial strains isolated from rhizosphere s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…A bulk of studies have suggested that the presence of PSBs can increase a plant’s tolerance to various abiotic stresses (e.g., drought, salinity, and nutrient deficiency) [ 56 , 57 ]. PSB have been isolated from the rhizosphere of several plants, including wheat [ 58 ], corn [ 59 ] and rice [ 60 ]. However, only few studies have reported on the PSB associated with quinoa roots [ 46 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…A bulk of studies have suggested that the presence of PSBs can increase a plant’s tolerance to various abiotic stresses (e.g., drought, salinity, and nutrient deficiency) [ 56 , 57 ]. PSB have been isolated from the rhizosphere of several plants, including wheat [ 58 ], corn [ 59 ] and rice [ 60 ]. However, only few studies have reported on the PSB associated with quinoa roots [ 46 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is due to the fact that about 95% of phosphorus is present in insoluble form in soils, where the plant only can absorb phosphate in soluble form [4]. The phosphorus also forms strong bonds with calcium and magnesium in alkaline soil pH; and with iron and aluminium in acidic soils [5]. Hence, it subsequently causes the mobility of phosphorus in soil to plants become very slow progress.…”
Section: Introductionmentioning
confidence: 99%
“…However, the focus is mainly on looking for beneficial effect of PSBs to plants, such as some PSBs can convert insoluble forms of nutrients into soluble forms, so the plants can take it up. Subsequently, it is enhancing the growth of plants, including faster ripening of fruits and flowering, also supports the immune system [5]. The phosphorus solubilization ability of bacteria is routinely screened by Pikovskaya (PK) medium that incorporated with tricalcium phosphate (Ca 3 (PO 4 ) 2 ) [10], which is a differential medium.…”
Section: Introductionmentioning
confidence: 99%